2013
DOI: 10.4269/ajtmh.12-0467
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Resistance Allele Frequencies in Anopheles gambiae before and after Anti-Vector Interventions in Continental Equatorial Guinea

Abstract: Abstract. Anti-malaria interventions that rely on insecticides can be compromised by insecticide-resistance alleles among malaria vectors. We examined frequency changes of resistance alleles at two loci, knockdown resistance (kdr) and acetylcholinesterase-1 (ace-1), which confer resistance to pyrethroids and DDT, and carbamates, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Our data was similar to previous investigations conducted across West Africa supporting the implication of metabolic mechanisms in carbamate resistance [27]. Although G119S mutation is recognized as the primary resistance mechanism against carbamates and organophosphates it remains less expanded across Central Africa [54]. Its distribution might be constrained by its high fitness cost [39].…”
Section: Discussionsupporting
confidence: 90%
“…Our data was similar to previous investigations conducted across West Africa supporting the implication of metabolic mechanisms in carbamate resistance [27]. Although G119S mutation is recognized as the primary resistance mechanism against carbamates and organophosphates it remains less expanded across Central Africa [54]. Its distribution might be constrained by its high fitness cost [39].…”
Section: Discussionsupporting
confidence: 90%
“…In Yengue the combined pre-intervention frequencies of these two alleles was already 90.4% and increased only slightly to 93.5%. However, kdr frequencies were low in Ukomba prior to the intervention (19.7%) and increased dramatically to 97.5% after the intervention [36].…”
Section: Discussionmentioning
confidence: 90%
“…gambiae (S) population in Mongomo, which was subjected solely to pyrethroids through the distribution of LLINs also experienced a sharp decline, even though kdr frequencies were high before the control started (90%±13.2%) [36]. Although a decline in efficacy of pyrethroid based IRS and ITN has been reported from Benin [38], most studies have actually found only a weak association between kdr and resistance against pyrethroids [Eg.…”
Section: Discussionmentioning
confidence: 99%
“…The results were complemented with data from the health information system (HIS) for 2009 and 2010 and entomological monitoring using light traps and human landing catches from 2007, 2009, 2010 and 2011 [12]. …”
Section: Methodsmentioning
confidence: 99%